B175 Evaluating the implementation of regional anaesthesia with virtual reality. (11th August 2022) - Ko, SSW; Potter, T; Zucco, L; Zaky, M; Pawa, A
Abstract : Background and Aims: Virtual Reality (VR) has been shown to reduce anxiety and pain scores for medical procedures, and in conjunction with regional anaesthesia (RA), has been reported to reduce sedation requirements, and improve patient satisfaction(1). We aimed to implement the use of VR for patients undergoing awake upper limb surgery under RA at our institution. Methods: Three Occulus Quest 2 VR headsets were kindly donated from Sintetica. The implementation process required several steps; local approval from clinical engineering and infection control to permit the use of these headsets on patients; establishing and troubleshooting the VR set up, which required disabling the boundary limit in order to have continuous use of the headset regardless of patient positioning; selecting appropriate media which included videos and immersive experiences. Patients who agreed to trial the VR headset were then asked for feedback. Results: The implementation of VR into our practice required technical preparation as well as local engagement to ensure multi-disciplinary awareness and buy-in, in particular from our ODPs and surgical colleagues. Initial feedback from surgeons and patients is positive, with reports noting the improved experience with VR in those with a history of previous surgeries under RA. Others noted the preferred media selection for future occurrences, such as documentaries or relaxing experiences, being mindful of which may result in nausea. Conclusions: A larger cohort of patients is required to evaluate the impact of VR as an adjunct to awake surgery on patient experience, but our preliminary service evaluation has provided very promising results.